On-Farm Trials of Pusa Vishal Mungbean in Vaishali District of Bihar - Sharma, S. N. (Indian Farming, 2015)
Success of summer mungbean in a cropping system mainly depends on selection of suitable short duration variety. The rapid adoption of improved mungbean varieties is a true transformation for a win-win situation for farmers, traders, consumers especially the poor. The results of the present study showed that mungbean variety like Pusa Vishal gave more than two-fold yield than local varieties.